Development of soapstock processing technology to ensure waste-free and safe production - Kalyna, V. N.; Koshulko, Vitalii; Ilinska, O. V.; Tverdokhliebova, Natalia; Tolstousova, Oksana; Bliznjuk, O. N.; Gavrish, Tatiana; Stankevych, Sergij; Zabrodina, Inna; Zhulinska, Oksana (Технологічний центр, 2021)
Soapstock is a large-tonnage waste of the oil and fat industry, the disposal of which is environmentally hazardous. Processing of soapstock into industrially valuable products, in particular, fatty acids, is promising. The method for producing fatty acids, which consists in sequential saponification of soapstock with sodium hydroxide solution, salting out with sodium chloride and decomposition with sulfuric acid solution has been investigated. The feature of this work is the study of the effect of salting out conditions of saponified soapstock on the yield and neutralization number of fatty acids. As an experimental sample, sunflower soapstock was used, the indicators of which correspond to DSTU 5033 (CAS 68952-95-4): mass fraction of total fat – 67.3 %, fatty acids – 61.8 %, neutral fat – 5.5 %. Soapstock was subjected to preliminary saponification under the following conditions: duration 85 min., concentration of sodium hydroxide solution 45 %. After that, the saponified mass was subjected to salting out. The obtained core soap was decomposed with the sulfuric acid solution under the following conditions: temperature 90 °C, duration 40 min. Rational salting out conditions were determined: duration (80 min.) and sodium chloride concentration (16 %). Under these conditions, the fatty acid yield is 95.0 %, the neutralization number is 194.8 mg KOH/g. The resulting fatty acids comply with DSTU 4860 (CAS 61788-66-7): the mass fraction of moisture and volatiles is 0.85 %, the mass fraction of total fat is 98.9 %, cleavage depth is 94.2 % oleic acid. This method of soapstock processing increases the fatty acid yield by 3.5 % compared to the method with saponification and decomposition, by 20.3 % compared to the method of soapstock decomposition with sulfuric acid. At the same time, the neutralization number increases by 4.1 % and 8.2 %, respectively. The improved method for fatty acids producing from soapstock provides highquality fatty acids with increased yield.

Соапсток є багатотоннажним відходом олієжирової галузі, утилізація якогоє екологічно небезпечною. Перспективною є переробка соапстоку на цінні для промисловості продукти, зокрема, жирні кислоти. Досліджено спосіб одержання жирних кислот, який полягає в послідовно-муомиленні соапстоку розчином натрій гідроксиду, висолюванні натрій хлоридом та розкладанні розчином сірчаної кислоти. Особливістю роботи є дослідження впливу умов висолювання омиленого соапстоку на вихід та число нейтралізації жирних кислот. В якості дослідного зразку використано соняшниковий соапсток, показники якого відповідають ДСТУ 5033 (CAS 68952-95-4): масова частка загального жиру – 67,3 %, жирних кислот – 61,8 %, нейтрального жиру –5,5 %. Соапсток піддавали попередньому омиленню за умов: тривалість 85 хв., концентрація розчину натрій гідроксиду 45 %. Після цього омилену масу піддавали висолюванню. Одержане ядрове мило розкладали розчином сірчаної кислоти за умов: температура 90°С, тривалість 40 хв. Встановлено раціональні умови висолювання: тривалість (80 хв.) та конентрацію натрій хлориду (16 %). За цих умов вихід жирних кислот становить 95,0 %, число нейтралізації – 194,8 мг КОН/г. Одержані жирні кислоти відповідають ДСТУ 4860 (CAS 61788-66-7): масова частка вологи та летких речовин – 0,85 %, масова частка загального жиру – 98,9 %, глибина розщеплення – 94,2 % олеїнової кислоти. Даний спосіб обробки соапстоку дає можливість збільшити вихід жирних кислот на 3,5 % у порівнянні із способом з омиленням та розкладанням, на 20,3 % – у порівнянні із способом розкладання соапстоку сірчаною кислотою. При цьому число нейтралізації збільшується на 4,1 % та 8,2 % відповідно. Удосконалений спосіб одержання жирних кислот із соапстоку дозволяє виробляти жирні кислоти підвищеної якості із збільшеним виходом.
Розробка технології переробкисоапстоку для забезпечення безвідхідності та безпеки виробництва
Keywords: safe production; soapstock; fatty waste; soap mass; neutralization number; жирові відходи; соапсток; мильна маса; висолювання; жирні кислоти; число нейтралізації